A decision-making framework for facilitating inclusive business model design interventions between smallholder vertical farmers and small to medium-sized enterprises in Sub-Saharan Africa - Musakwa, Rodney (Stellenbosch : Stellenbosch University, 2025)
Musakwa, R. 2025. A Decision-Making Framework for Facilitating Inclusive Business Model Design Interventions between Smallholder Vertical Farmers and Small to Medium-Sized Enterprises in Sub-Saharan Africa. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/c72ffd36-7763-4331-b909-15a46d00c2b5